Disconnections and Laves (C14) precipitation in high-Cr ferritic stainless steels. (1st October 2020) - Chai, Yaw Wang; Kato, Ko; Yabu, Chieri; Ishikawa, Shin; Kimura, Yoshisato
Abstract: Even though it is widely accepted that the Laves phase is a promising strengthener for chromium-containing stainless steels, there is little information available on its microstructural evolution and growth. Therefore, in this study, we analysed the behaviour of Laves (C14) precipitates in high-Cr ferritic stainless steel, Fe-20Cr-2Mo-0.5Nb (at%), annealed at 1073 K for different time periods. A high density of (Fe, Cr)2 (Mo, Nb) precipitates was formed in the α matrix during annealing. Morphological evolution in the Laves phase followed the sequence of spheroidal → faceted ellipsoidal → faceted needle-like → faceted plate-like. The Laves phase is related to the α matrix by two sets of orientation relationships, viz. OR-1: [ 1 ¯ 1 ¯ 2 ] α / [ 1 2 ¯ 10 ] L, [ 111 ] α / [ 0 1 ¯ 10 ] L, and ( 1 ¯ 10 ) α / ( 000 1 ¯ ) L and OR-2: [ 1 1 ¯ 0 ] α / [ 0001 ] L, [ 113 ] α / [ 1 ¯ 1 ¯ 20 ] L, and ( 3 ¯ 3 ¯ 2 ) α / ( 1 1 ¯ 00 ) L . The habit plane of the Laves phase was found to deviate slightly from the ( 3 ¯ 3 ¯ 2 ) α / ( 1 1 ¯ 00 ) L plane. Interfacial defects, namely disconnections ( b D, h ) and super disconnections ( m b D, mh ), observed experimentally along the habit plane, were consistent with theoretical results based on OR-2 as the reference coordinate frame. The Burgers vector b D exhibited an edge component b y D (0.1539 nm) parallel to Y / [ 113 ] α / [ 1 ¯ 1 ¯ 20 ] L and a small normal component b z D (0.0747 nm) perpendicular to the terraces; meanwhile, the overlap step height h = d ( 1 1 ¯ 00 ) L . The morphological evolution of Laves precipitates was described based on the lateral motion of disconnections and super disconnections on 3 ¯ 3 ¯ 2 α / 1 1 ¯ 00 L terraces in the 〈 113 〉 α / 〈 1 ¯ 1 ¯ 20 〉 direction. Arrays of the disconnections ( b D, h ) were found to be capable of accommodating the misfit strain on 3 ¯ 3 ¯ 2 α / 1 1 ¯ 00 L terraces. Graphical abstract: Image, graphical abstract